Nitrogen uptake of maize (Zea mays. L) from isotope-labeled biomass of Paraserianthes falcataria grown under controlled conditions - Chintu, R.; Zaharah, A.R. (Springer Science and Business Media LLC, 2003)
Roots can be an important though poorly quantified source of nitrogen (N) in agroforestry systems. Nitrogen uptake of maize using P. falcataria below- and aboveground biomass separately, and their combination, as source of N, was assessed in a controlled experiment using 15N isotope labeling techniques. The 15N-direct and the 15N-indirect labeling techniques were compared for discrepancies in measuring N cycling from P. falcataria tree residues. N contribution to maize production was as follows; 40-57% from below ground biomass and 10-18% from above ground biomass (P < 0.05). Residue N use efficiency (%rNE) by maize was between 99 and 106% for belowground biomass, 4-4.5% for aboveground biomass. This implies that though nutrient release characteristics of aboveground biomass are commonly used as a basis for selection of agroforestry trees, those of belowground biomass would be of fundamental importance as well. Combining P falcataria below and aboveground biomass did not result in significant (P < 0.05) effects on N recovered by maize, suggesting the absence of decomposition interactions between the two bio-chemically contrasting residues. There were no significant methodological differences reflected in measured N cycled by maize from leaves (Ndfr); 15% and 18% as estimated by 15N direct and indirect method, respectively. The two methods compared very well (P < 0.05) as tools of estimating N cycling from surface applied leaves. However, the ability of the direct method to measure N without disturbing either the tree or the soil, would make it a more attractive and valuable tool in N cycling studies in agroforestry systems.